2020
DOI: 10.17352/2455-2968.000084
|View full text |Cite
|
Sign up to set email alerts
|

Thyroidectomy under local anaesthesia in a poor resource health facility in Northeastern Nigeria

Abstract: Background:The provision of quality health care is one of the priorities of every government. The quality of such care is however, limited by the human and technical resources available. The varying types of thyroidectomy for Goitres are often done under general anaesthesia, unless, there is a contraindication such as, cardiopulmonary instability. Recently, there is increasing evidence that thyroidectomy could be done under local anaesthesia with or without anxiolytics or opioid analgesia augmentation. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…This is similar to what was reported by other authors [9] [12] [13] [15] [17]. In a study conducted in Potiskum, Nigeria, the authors reported a mean duration of surgery of 40 minutes [16], much lower than what was observed in this study. But because most of these studies did not clearly define the period they consider as the duration of surgery, it is difficult to compare their findings.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is similar to what was reported by other authors [9] [12] [13] [15] [17]. In a study conducted in Potiskum, Nigeria, the authors reported a mean duration of surgery of 40 minutes [16], much lower than what was observed in this study. But because most of these studies did not clearly define the period they consider as the duration of surgery, it is difficult to compare their findings.…”
Section: Discussionsupporting
confidence: 91%
“…Ahmad and colleagues reported a female preponderance (22 females, and 8 males) in a cross sectional study of thyroid surgery under LA [13]. Similar findings of female preponderance among patients that had thyroidectomy under LA were also reported by other authors [14] [15] [16]. Eke et al did not report any male patient among the 15 patients with giant goiters who had thyroidectomies under LA in their study [9].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Henceforth due to drawbacks of GA, in the last two decades, there has been an increase in the number of thyroidectomies performed under regional/LA combined with monitored anesthesia care [ 11 , 13 ]. These numbers have even increased further with the development of minimally invasive thyroidectomy particularly in short-stay settings [ 9 ] and now, a few surgeons in the western world are currently doing thyroidectomies exclusively under LA [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other than overcoming the need to book for intensive care space and an anesthesiologist [ 14 ], which most patients in low-income countries cannot afford in the case of thyroidectomy under GA [ 15 ], LA has been associated with less post-operative pain, costs, hospital stay duration, post-operative nausea, vomiting, throat discomfort, and voice changes [ 9 , 16 , 17 ]. According to research in Nigeria [ 13 ], India [ 8 ], and USA [ 16 ], complications such as hematoma, surgical site infection, and colloid occur in less than 4% of cases of thyroidectomy performed under LA. In a randomized controlled study in Germany [ 9 ], the occurrences of post-operative complications (pain, nausea, vomiting, throat discomfort, painful swallowing, voice change, and difficulty in breathing were less in the group of patients who underwent thyroidectomy under LA as compared with those under GA in contrast to the prospective study in Uganda [ 18 ].…”
Section: Introductionmentioning
confidence: 99%